MENINGKATKAN BUDAYA MENULIS BAGI PENULIS MUDA: Beberapa Catatan Terhadap Sebuah Kursus Kepenulisan - Raichul Amar (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
The Research and Publishing Center (LPPM) of UIN Imam Bonjol Padang on May 4, 2017 held a Short-Course for Writing Scientific Work as an effort to arouse the spirit and tradition of writing for young writers on campus. Academically and intra-curricularly, debriefing theoretical and technical abilities has been passed through lectures on Research Methods in field training / assignments. But it turns out that there are still many resources that have not yet become true, capable and fluent in applying research design. The training participants consisted of students from the undergraduate and postgraduate programs of UIN Imam Bonjol Padang from various departments / faculties. Active participants who have made activities using 29 final works of writing. From the collection of texts the participants of the short course in general can be seen as follows: a. The theme of Writing Culture, a theme that has a tangent point in scientific substance, the theme of bodies, zombies and humans.